Construction Protocol of Wireless Sensor Network based on Centralized Clustering Routing and Time Division Multiplexing MAC Protocol - Shitao Yan; Mianrong Yang (Institute of Advanced Engineering and Science, 2014)
LEACH is a routing protocol based on clustering in wireless sensor networks and is based on a low power adaptive hierarchical routing algorithm design of wireless sensor network. Time division multiplexing mechanism is for each wireless sensor network node distribution independent time slots for data transceiver, and the node into sleep state in other free time slot. This paper introduces MAC protocol based on time division multiplexing. The paper proposes construction protocol of wireless sensor network based on centralized clustering routing and time division multiplexing MAC protocol. The simulation results show that the LEACHEE protocol can effectively reduce network energy consumption, prolong the network life cycle.